The Influence of Production Factors on The Income Level of Rice Farmer in The Rambutan Banyuasin District - Agustine, Fyra; Purba, Yudhi Zuriah Wirya; Thanomutiara, Eka (Journal of Science and Science Education, 2025)
This study examines the influence of key production factors—land area, NPK fertilizer usage, and labor—on the income level of rice farmers in Rambutan District, Banyuasin Regency, with production output considered as a mediating variable. Data were collected through a combination of primary surveys and secondary sources, and analyzed using Path Analysis to determine direct effects, while indirect effects were tested using the Sobel method. The analysis reveals that land area and NPK fertilizer have a significant and positive direct effect on production, whereas labor does not show a significant contribution. Furthermore, land area, NPK fertilizer, labor, and production each exert a direct influence on farmers’ income. However, the mediating role of production between the production factors and income is found to be statistically insignificant. These findings suggest that income improvements are more strongly driven by direct inputs—particularly land and fertilizer—than by production gains alone, underscoring the importance of resource allocation in farming strategies.